Exercise-induced mitophagy in skeletal muscle occurs in the absence of stabilization of Pink1 on mitochondria. Issue 1 (2nd January 2019) - Drake, Joshua C.; Laker, Rhianna C.; Wilson, Rebecca J.; Zhang, Mei; Yan, Zhen
ABSTRACT: Maintenance of mitochondrial quality is essential for skeletal muscle function and overall health. Exercise training elicits profound adaptations to mitochondria to improve mitochondrial quality in skeletal muscle. We have recently demonstrated that acute exercise promotes removal of damaged/dysfunctional mitochondria via mitophagy in skeletal muscle during recovery through the Ampk-Ulk1 signaling cascade. In this Extra View, we explore whether Pink1 is stabilized on mitochondria following exercise as the signal for mitophagy. We observed no discernable presence of Pink1 in isolated mitochondria from skeletal muscle at any time point following acute exercise, in contrast to clear evidence of stabilization of Pink1 on mitochondria in HeLa cells following treatment with the uncoupler carbonyl cyanide m-chlorophenyl hydrazone (CCCP). Taken together, we conclude that Pink1 is not involved in exercise-induced mitophagy in skeletal muscle.